Parametric study of midplane gas puffing to maximize ICRF power coupling in ITER. (1st March 2023) - Zhang, W.; Messiaen, A.; Helou, W.; Bobkov, V.; Lamalle, P.; Pitts, R.A.; Tierens, W.
Abstract: Midplane gas puffing close to the ion cyclotron range of frequencies (ICRF) antennae has been demonstrated to be robust in improving ICRF power coupling in current tokamaks. It is also shown in a previous study (Zhang 2019 Nucl. Mater. Energy 19 364–71) that in ITER, midplane gas puffing with a puff rate of ∼4.5 × 10 22 electrons s −1 can increase the antenna loading/coupling resistance by about a factor of two. In this paper, a comprehensive parametric study has been carried out to characterize the influence of midplane gas puffing on ICRF power coupling in additional and broader range of parameter scans. The new parameter scans include the gas puff rate, the poloidal location of the gas pipe orifices (GPOs), the separatrix density, the particle perpendicular diffusion coefficient, the radial distance between the plasma and antenna as well as the antenna phasing. The 3D edge plasma fluid and neutral transport code EMC3-EIRENE code has been used to simulate the 3D distributions of plasma density in the presence of gas puffing, which are then used in the antenna code ANTITER II to calculate the antenna coupling. The simulation results indicate that the ITER ICRF local midplane gas injection layout (with the GPOs located on one side of each antenna port) increases the ICRF power coupling significantly in all studied plasma scenarios and antenna parameters. We are hence confident that the chosen layout for the ICRF local gas injection on ITER is appropriate. We are also confident that the ITER local gas injection will allow boosting the ICRF coupling with all studied plasma conditions and antenna phasings.